Mobility analytics for spatio-temporal and social data : First International Workshop, MATES 2017, Munich, Germany, September 1, 2017, Revised Selected Papers /: First International Workshop, MATES 2017, Munich, Germany, September 1, 2017, Revised Selected Papers. ([2018]) - Unknown
No abstract available